Ultra maniac. Vol. 2 - Yoshizumi, Wataru (Viz, 2005)
Ayu learns how fickle and uncontrollable--even by magic--love can be when Yuta, a new student from Nina's home dimension, gives her a camera he claims can reveal true love.